2020
DOI: 10.1103/physreva.102.020402
|View full text |Cite
|
Sign up to set email alerts
|

Maximal-steered-coherence protection by quantum reservoir engineering

Abstract: We show that the effects of decoherence on quantum steering ellipsoids can be controlled by a specific reservoir manipulating, in both Markovian and non-Markovian realms. Therefore, the socalled maximal steered coherence could be protected through reservoir engineering implemented by coupling auxiliary qubits to the reservoir.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 36 publications
(37 reference statements)
0
20
0
Order By: Relevance
“…As a result, quantum entanglement is the key to unify these two settings and lay out a general formalism for quantum complementarity. Our study, illuminating the deep connection between quantum eraser protocols and wave-particleentanglement triality, may shed new light on fundamental aspects of quantum interferometry [22], quantum coherence, and quantum steering [33].…”
Section: Duality−entanglement Relationmentioning
confidence: 97%
“…As a result, quantum entanglement is the key to unify these two settings and lay out a general formalism for quantum complementarity. Our study, illuminating the deep connection between quantum eraser protocols and wave-particleentanglement triality, may shed new light on fundamental aspects of quantum interferometry [22], quantum coherence, and quantum steering [33].…”
Section: Duality−entanglement Relationmentioning
confidence: 97%
“…Recently, a quantum-reservoir-engineering approach [21] i.e. by adding some auxiliary qubits to the reservoir has been suggested to protect entanglement [21][22][23][24][25], coherence [26][27][28][29] and the entropic-uncertainty lower bound [30]. Up until now, we have not seen any reports for the quantum reservoir engineering approach on the protection of quantum discord against decoherence.…”
Section: Introductionmentioning
confidence: 99%
“…The QSE provides a novel avenue to visually investigate and capture various quantum nonlocalities [30]. Due to these interesting properties, a variety of promising works has been achieved [28][29][30][31][32][33][34][35][36][37][38]. By using the QSE, Jevtic et al [28] proposed the condition of nested tetrahedron to prove whether a quantum state is separable.…”
Section: Introductionmentioning
confidence: 99%
“…The generalized QSE for a qubit-field system was characterized by Athulya et al [36]. Maleki et al [37] investigated the protection of maximal steered coherence through the QSE. Recently, considering the XXZ model, Du et al [38] revealed the quantum phase transitions via the QSE, and found the relation between the QSE and quantum phase transitions.…”
Section: Introductionmentioning
confidence: 99%